Code-Mixing in Sabah and Sarawak English Short Stories - Fazira Bukas, Charlie; Yvonne Michelle, Campbell (UNIMAS Publisher, 2023)
This research delves into the phenomenon of code-mixing as observed in a carefully selected corpus of English short stories from Sabah and Sarawak, Malaysia. The investigation encompasses an in-depth analysis of the various displays of code-mixing present in these literary works, while also offering insights into the underlying motivations for code-mixing occurrences. A total of 20 short stories were selectedfrom the anthologies "Chronicles of KK" and "Short Stories from Sarawak: Death of a Longhouse & Other Stories." Employing a qualitative research methodology, the study draws upon theoretical frameworks provided by Musyken (2000) and Hoffman (1991) to scrutinize the linguistic data. The research discerns two prominent types of code-mixing, namely insertion and alternation, with insertion emerging as the predominant form, notably incorporating lexical elements from the local and Indigenous languages of Sabah and Sarawak. The findings illuminate that code-mixing is strategically employed in these narratives to address specific thematic content, enhance comprehensibility for the interlocutor, signify group identity, facilitate repetition for clarification, and serve as a means of interjection. This study contributes to a richer understanding of the intricate dynamics of code-mixing in the literary context of these regions.